Magnesium transport in the cortical thick ascending limb of Henle's loop of the rabbit. - Shareghi, G R (1982)
Isolated cortical thick ascending limbs of Henle's loop were perfused in order to directly evaluate magnesium transport in this segment. Transepithelial potential difference was altered by varying the NaCl concentration in perfusate and bath and adding 50 microM furosemide to the perfusate. Perfusion under standard conditions with isotonic solutions resulted in a mean transepithelial potential difference of +8.8 +/- 0.7 mV and net magnesium absorption at a rate of 0.32 +/- 0.06 pmol/mm per min. Perfusion with a hypotonic solution significantly increased potential difference and the net absorptive rate of magnesium, calcium, and potassium. Conversely, reversal of the polarity of the potential difference with low NaCl bath and luminal furosemide produced net secretion of magnesium, calcium, and potassium. Parathyroid hormone in a bath concentration of 1.0 U/ml increased magnesium absorption from 0.32 +/- 0.06 to 0.63 +/- 0.06 pmol/mm per min (P less than 0.001) and calcium from 0.52 +/- 0.08 to 0.97 +/- 0.08 pmol/mm per min (P less than 0.001). Dibutyryl cyclic AMP produced similar effects on both calcium and magnesium absorption. Increasing bath calcium concentration twofold significantly inhibited net calcium absorption from 0.79 +/- 0.27 to 0.16 +/- 0.02 pmol/mm per min but magnesium transport was unaffected. Increasing bath magnesium concentration twofold significantly inhibited net magnesium absorption from 0.56 +/- 0.14 to -0.09 +/- 0.13 pmol/mm per min but had no effect upon net calcium transport. Net absorption of magnesium was significantly increased with increased concentration in the perfusate but calcium transport was unchanged. Similarly, increasing perfusate calcium concentration produced an increase in net calcium transport but did not alter magnesium transport. These data indicate that this segment of the loop of Henle is an important site for magnesium transport. Transport is influenced by luminal and bath concentration and is stimulated by parathyroid hormone and cyclic AMP. The data do not provide support for the concept of an interactive process between calcium and magnesium, and suggest that the positive transepithelial voltage is an important driving force for net reabsorption of magnesium, as well as calcium and potassium in this segment.